Contact resistance between two REBCO tapes under load and load cycles. (21st February 2017) - Lu, Jun; Goddard, Robert; Han, Ke; Hahn, Seungyong
Abstract: No-insulation (NI) REBCO magnets have many advantages. They are self-protecting, and therefore do not need quench detection and protection, which can be very challenging to implement in a high T c superconducting magnet. Moreover, by removing the insulation and allowing thinner copper stabilizers, NI REBCO magnets have significantly higher engineering current density and higher mechanical strength. On the other hand, NI REBCO magnets have the drawbacks of long magnet charging time and high field ramp loss. In principle, these drawbacks can be mitigated by managing the turn-to-turn contact resistivity ( R c ). Evidently, the first step toward managing R c is to establish a reliable method of accurate R c measurement. In this paper, we present experimental R c measurements for REBCO tapes as a function of mechanical load up to 144 MPa and load cycles up to 14. We find that R c is in the range of 26–100 μ Ω·cm 2, and that it decreases with increasing pressure, and gradually increases with the number of load cycles. The results are discussed in the framework of Holm's electric contact theory.